HUBUNGAN SUPERVISI OLEH KEPALA SEKOLAH DAN KOMPETENSI GURU DENGAN KEPUASAN KERJA DI SEKOLAH DASAR NEGERI SE-KECAMATAN BASO KABUPATEN AGAM - Adi Warman (IAIN Batusangkar, 2016)
The purpose of this research was to reveal how extend the correlations of Supervision by the Principal and teacher Competencywith job satisfaction at elementary schools in Baso districk Agam.This research used quantitative method which shows the reality and many problems appeared.The population of this research was 201 persons of all elementary schools teachers in distric Baso. Numbers of samples of this research were 60 persons.This research revealed are (1) Supervision by the principal correlated with job satisfaction significantly. The extended of correlation of job satisfaction determined by Supervision ofthe principal as 22 %. (2) Teacher competency correlated with job satisfsction significantly. Job satisfaction was determined by teachers teacher competency as 19,4 %. (3) The supervision by the principal (X1)and teacher comptetency (X2) correlated significantly with job satisfaction at elementary schools in Baso districk Agam, and the extend job satisfsction was determined by supervision the principal and teachers’ competency as 29,1 %.Key Words: Supervisi, kemampuan guru, kepuasan kerja